MINIX4RT: Real-time Semaphores - Pessolani, Pablo Andrés (2008)
MINIX4RT is an extension of the well-known MINIX Operating System that adds Hard Real-Time services in a new microkernel but keeping backward compatibility with standard MINIX versions. Semaphores are the primitive synchronization and mutual exclusion mechanism in many operating systems, but MINIX does not provide those facilities. Semaphores were added to MINIX4RT, and since it is a Real-Time Operating System, they must meet some processing requirements such as dequeueing waiting processes in priority order and avoiding the Priority Inversion problem. This article describes the Real-Time Semaphores facilities available on MINIX4RT, its design, implementation, performance tests and their results.